KONSEP HUMANISME YUNANI KUNO DAN PERKEMBANGANNYA DALAM SEJARAH PEMIKIRAN FILSAFAT - Hadi, Sumasno (Jurnal Filsafat "WISDOM", 2012)
Humanism is a philosophical view that upholds values and positions of human and make it as a criterion of all things. Humanism has its main object that is human nature, its limits and natural tendencies. Humanism as a term in the intellectual history has always highlighted problems of humanity that is often used in the study of philosophy. Humanism as an intellectual movement emerged in the Renaissance era which roots in Ancient Greece. Two main points of the Ancient Greek civilization as sources of humanism concept are a philosophical development from problems of nature (cosmological) into discussion about problems of human (anthropological); and the concept of "paideia" as the Ancient Greek education system that becomes the beginning of human consciousness and intellectual, and also a reflection of human existence in the form of reason.